Allah and me: learning to live Allah's way - Rahman, Vinni; Gurmeet (Goodword Books New Delhi, 2017)
Allah knows what is best for us. Read this book to know what He expects from us and what He likes and dislikes. Allah and Me is a book which discusses some Islamic virtues which we should practice in our daily life in order to live according to Allah's will and become candidates for Paradise. A Muslim does everything for Allah. Every Little Talk in this book includes some questions to make children think, especially about their own behavior in context of the virtue discussed in that Talk. Each Talk ends with some Quranic verses and Hadith quotes to stress and highlight the Islamic teaching discussed in that Talk.